2003
DOI: 10.1145/949343.949322
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cross-platform optimizations for a java just-in-time compiler

Abstract: This paper describes the system overview of our Java Just-In-Time (JIT) compiler, which is the basis for the latest production version of IBM Java JIT compiler that supports a diversity of processor architectures including both 32-bit and 64-bit modes, CISC, RISC, and VLIW architectures. In particular, we focus on the design and evaluation of the cross-platform optimizations that are common across different architectures. We studied the effectiveness of each optimization by selectively disabling it in our JIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
10
0
5
Order By: Relevance
“…A number of factors, such as optimization capabilities within the system, the trade-off between performance and compilation overhead for each optimization, the classification of optimizations to each level, and the profiling and method promotion system, can affect the decision. In our case, we conducted a number of experiments for evaluating the performance contribution and the compilation overhead for each optimization [Ishizaki et al 2003]. Figure 4 shows various data for compilation overhead: compilation time, compiled code size, and peak compiler memory use for the three optimization levels.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors, such as optimization capabilities within the system, the trade-off between performance and compilation overhead for each optimization, the classification of optimizations to each level, and the profiling and method promotion system, can affect the decision. In our case, we conducted a number of experiments for evaluating the performance contribution and the compilation overhead for each optimization [Ishizaki et al 2003]. Figure 4 shows various data for compilation overhead: compilation time, compiled code size, and peak compiler memory use for the three optimization levels.…”
Section: Discussionmentioning
confidence: 99%
“…An instance allocation statement that allocates an instance used only to store values. In this case, we can eliminate the instance allocation statement and all the statements that store a value in the instance, because nothing refers to the stored value [5,6].…”
Section: Related Workmentioning
confidence: 99%
“…Inlining can be counted among the most effective optimizing program transformations for a variety of programming languages, with examples of execution time improvements of 5 to 28% [18] for CLU 15% [8] for C code, 24% [4] for intermediate code, and 10 to 44% [13] or up to 40% [2] for Java programs.…”
Section: Related Workmentioning
confidence: 99%
“…Ishizaki et al [13] reported that inlining only very small methods gave performance improvements to within 15% of the peak performance, while increasing compilation time by only 6% on average. On the other hand, in order to obtain the peak performance, an increase of compile time by up to 50% had to be accepted.…”
Section: Related Workmentioning
confidence: 99%